Verso il 50° del Convegno sui “mali di Roma” del febbraio 1974 - D’Angelo, Augusto (Studi Politici, 2023)
The contribution turns its attention to an event which, on the eve of the 50th anniversary of its realization, analyzes a very different season in terms of level of participation and debate on the destiny of the city: the conference “The responsibility of Christians in front of the expectations of charity and justice in the city of Rome” which was held in February 1974, which then went down in history as the conference “on the evils of Rome”.